2020
DOI: 10.1002/ase.1993
|View full text |Cite
|
Sign up to set email alerts
|

Dissection versus Prosection: A Comparative Assessment of the Course Experiences, Approaches to Learning, and Academic Performance of Non‐medical Undergraduate Students in Human Anatomy

Abstract: Many institutions rely upon prosection‐based laboratories as more resource‐efficient and time‐effective alternatives to traditional cadaver dissection for human anatomy education. To facilitate growing enrollment numbers despite resource limitations, the University of Guelph (a non‐medical institution) introduced a modified “stepwise” prosection‐based laboratory cohort to supplement a dissection‐based course. In this design, all students attended the same lectures, but those in the dissection‐based cohort lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 80 publications
(216 reference statements)
1
27
0
Order By: Relevance
“…Viewing physical structures with true stereopsis has been shown to be crucial to learning in human anatomy (Wainman et al, 2018(Wainman et al, , 2020, especially for students with low visuospatial abilities (Cui et al, 2017;Bogomolova et al, 2020;Meyer & Cui, 2020;Roach et al, 2021). Furthermore, in-person laboratory environments have been shown to promote deep rather than surface approaches to learning in anatomy (Smith & Mathias, 2010;McWatt et al, 2021), which are associated with higher quality learning outcomes (Pandey & Zimitat, 2007). It is possible that the loss of these features from the course learning activities had a negative impact on students' confidence in their anatomy knowledge and spatial understanding, both of which were reflected in the students' complaints about being tested on cadaveric images in this study and among other groups (Singal et al, 2021).…”
Section: Assessmentmentioning
confidence: 99%
“…Viewing physical structures with true stereopsis has been shown to be crucial to learning in human anatomy (Wainman et al, 2018(Wainman et al, , 2020, especially for students with low visuospatial abilities (Cui et al, 2017;Bogomolova et al, 2020;Meyer & Cui, 2020;Roach et al, 2021). Furthermore, in-person laboratory environments have been shown to promote deep rather than surface approaches to learning in anatomy (Smith & Mathias, 2010;McWatt et al, 2021), which are associated with higher quality learning outcomes (Pandey & Zimitat, 2007). It is possible that the loss of these features from the course learning activities had a negative impact on students' confidence in their anatomy knowledge and spatial understanding, both of which were reflected in the students' complaints about being tested on cadaveric images in this study and among other groups (Singal et al, 2021).…”
Section: Assessmentmentioning
confidence: 99%
“…The preference for a hybrid model even assuming no health risk was surprising, as cadaveric dissection is generally considered not only a rite of passage, but also the most effective method of anatomical education (Granger, 2004 ; Winkelmann, 2007 ; Ghosh, 2017 ; Franchi, 2020 ; Ross et al, 2021 ; Zibis et al, 2021 ). Students may prefer a hybrid model because it allows them to spend more time studying at home, easing the adjustment to medical school (Cuddy et al, 2013 ; Kinirons et al, 2019 ; McWatt et al, 2021 ). Nevertheless, in spite of the given health risk posed by Covid‐19, students still preferred to retain some form of in‐person cadaveric learning in the form of prosections.…”
Section: Discussionmentioning
confidence: 99%
“…Foreign Medical Graduate Program status, anatomy session, sex, age, ethnicity, individuals residing in primary residence, and previous gross anatomy experience were included in the models as fixed effects. As many studies have demonstrated that a student's preconceived notions about gross anatomy often influence their perception of the course overall (Kerby et al, 2011 ; Jeyakumar et al, 2020 ; McWatt et al, 2021 ), students' response to “Assuming no health risk to yourself or others, what would be your ideal method of learning anatomy?” was also included as an additional fixed effect in the model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most research related to deep approaches to learning have focused on its relationship to achievement and involved mostly students above the age of six ( Fryer and Vermunt, 2018 ; Khan et al, 2018 ; Rentzios et al, 2019 ; Chan et al, 2021 ; McWatt et al, 2021 ; Piumatti et al, 2021 ). For example, Duff et al (2004) examined the cross-sectional relationship between deep approaches to learning and grade-point average among undergraduate students using a structural equation modeling analysis.…”
Section: Deep Approaches To Learningmentioning
confidence: 99%